The Influence of Quality of Work Life and Perceived Organizational Support on Turnover Intention in Private Higher Education Institutions - Zeng, Dongxiu; Swatdikun, Trairong; Aujirapongpan, Somnuk; Huang, Shi-Zheng (Emerging Science Journal, 2024)
The study addresses faculty turnover in private higher education institutions, a challenge that disrupts institutional progress and educational continuity. It examines the influence of Quality of Work Life (QWL) on turnover intention (TI) and the mediating role of Perceived Organizational Support (POS). Utilizing a stratified random sample of 396 educators across 24 private colleges, data were collected through structured questionnaires and analysed using Structural Equation Modeling (SEM). The findings reveal a significant negative relationship between QWL and TI, indicating that improved work-life balance reduces educators' intent to resign. Additionally, QWL positively influences POS, which further diminishes TI, with POS mediating the QWL-TI relationship. By integrating POS as a mediator, the study provides actionable insights for educational administrators, emphasizing the importance of enhancing QWL and POS to mitigate faculty turnover. The findings offer a foundation for developing targeted policies aimed at improving workplace conditions and organizational support to ensure institutional stability. Doi: 10.28991/ESJ-2024-SIED1-020 Full Text: PDF